Isolation, production and characterization of bioactive metabolites from endophytic bacterial isolates - Lal, Moti (My University, 2019)
Endophytes are group of microoganisms that are found in various parts of plant tissue without causing any symptoms of the disease. most endophytes try to live life by a symbiotic relationship with the host plant. Plant endophytic bacteria, like their host plants, have a large and special capacity to product a variety of bioactive metabolites at large levels, through which it protects its host from various diseases and natural calamities
Keywords: Isolation production; Characterization bioactive metabolites